2022
DOI: 10.1183/13993003.02531-2021
|View full text |Cite
|
Sign up to set email alerts
|

Increased cytotoxic T-cells in the airways of adults with former bronchopulmonary dysplasia

Abstract: RationaleBronchopulmonary Dysplasia (BPD) in preterm born infants is a risk factor for chronic airway obstruction in adulthood. Cytotoxic T-cells are implicated in chronic obstructive pulmonary disease (COPD), but their involvement in BPD is not known.ObjectivesTo characterise the distribution of airway T-cell subsets in adults with a history of BPD.MethodsYoung adults with former BPD (n=22; median age 19.6 years), age-matched adults born preterm (n=22), patients with allergic asthma born at term (n=22), and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…1,2 Approximately 10-30% premature infants who were born with <1000 g birthweight before 30 weeks' gestation would have the potential to develop BPD. 3 Mounting evidences have demonstrated that BPD is associated with considerable morbidity and mortality in the newborn period, childhood, and adulthood. 4,5 In addition to the respiratory system, BPD also shows adverse impacts on the neurodevelopment and other organs throughout the body.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Approximately 10-30% premature infants who were born with <1000 g birthweight before 30 weeks' gestation would have the potential to develop BPD. 3 Mounting evidences have demonstrated that BPD is associated with considerable morbidity and mortality in the newborn period, childhood, and adulthood. 4,5 In addition to the respiratory system, BPD also shows adverse impacts on the neurodevelopment and other organs throughout the body.…”
Section: Introductionmentioning
confidence: 99%
“…This approach captures participants moving from relatively low-risk to high-risk subgroups of future diseases, such as chronic obstructive pulmonary disease. As highlighted by Guo and colleagues, and also discussed elsewhere ( 5 ), this highlights the importance of taking the heterogeneity of processes that can lead to chronic airway obstruction into account (e.g., bronchopulmonary dysplasia after preterm birth as one specific example) ( 6 ). Whether the growth failure group will experience the same (or different) lung aging process as the persistently low group needs to be explored in future studies ( 7 ).…”
mentioning
confidence: 89%
“…The chronic inflammation in BPD subjects [43,44], and the normal levels of FeNO (a marker of eosinophilic inflammation) in children born preterm suggest that the inflammatory mechanisms in their airways differ from the eosinophilic inflammation of childhood asthma, raising questions over the long-term use of inhaled corticosteroids for BPD patients [45]. Research on the efficacy of these drugs in preterm-born children is still ongoing [46], but there is still no evidence to support their background use [47].…”
Section: Treatments Available Beyond the Neonatal Periodmentioning
confidence: 99%